What Are the Predictors of Acute Care Nurses' Stroke Knowledge?: Empirical Research Quantitative - Catherine T. Leach; Linda P. Bolin; Melvin S. Swanson; Ashley E. Burch; Patricia C. Woltz (Nursing Open)
ABSTRACT Aims To examine the predictability of categorical and quantitative study variables on acute stroke knowledge amongst study participants. Design Non‐experimental, descriptive correlational. Methods A convenience sample of registered nurses caring for adult, hospitalized patients recruited from the urban Southeast. A three‐part survey was emailed to the nurses: demographics, stroke education and experience, and the Acute Stroke Management Questionnaire. Results Intensive Care Unit and Emergency Department nurses had the highest level of stroke knowledge. Nurses reporting three or more post‐licensure education modalities had higher stroke knowledge scores than those reporting two or less. Practice setting, self‐perception of stroke knowledge, self‐identified knowledge of acute stroke management and three items related to code stroke were significantly correlated with stroke knowledge. Conclusion Various methods of training and reinforcement of learning using varying teaching styles are effective in increasing nurses' stroke knowledge. Further stroke education is needed for nurses across the acute care setting. Implications Future studies should explore lived experiences of nurses to gain understanding of nonquantifiable factors that nurses feel have strengthened their stroke knowledge. Impact What Problem Did the Study Address? ○Addressing the gap in the knowledge of predictors of nurse stroke knowledge. Main Findings? Practice setting, post‐licensure stroke education, code stroke familiarity, confidence and understanding were all predictive of the overall stroke knowledge. Whom Will the Research Have an Impact? Nurses, nurse educators, patients experiencing and at risk for stroke. Reporting Method The STROBE checklist was used to strengthen the reporting of the results. Patient or Public Contribution Nurses voluntarily participated in this study by completing the online questionnaire. What Does This Paper Contribute to the Wider Global Clinical Community? Provides predictors of stroke knowledge for nurse leaders to have a better understanding of nurses' educational needs. Provides evidence of a quick, effective measure of nurses' stroke knowledge.